Different complexation behavior of a proton transfer compound obtained from 1,10-phenanthroline and pyridine-2,6-dicarboxylic acid with InIII and CeIII: Synthesis, crystal structures and solution studies - Ramezanipour, Farshid; Aghabozorg, Hossein; Shokrollahi, Ardeshir; Shamsipur, Mojtaba; Stoeckli-Evans, Helen; Soleimannejad, Janet; Sheshmani, Shabnam (My University, 2005)
The different complexation methods of a proton transfer compound LH2, (phenH)2 (pydc) (phen=1,10-phenanthroline; pydcH2=pyridine-2,6-dicarboxylic acid), are discussed and formation of [In2SO4 (pydc)2 (phen)2(H2O)2]•5.5H2O (1) and {[Ce(pydc)(pydcH)(H2O)2]•4H2O}n (2) are reported. The complexes were synthesized by reaction of LH2 with In2 (SO4)3•xH2O and Ce(NO3)3•6H2O, respectively. The characterization was performed using IR spectroscopy and X-ray diffraction. The complex 1 crystallizes in the space group РĪ of the triclinic system, with two molecules per unit cell. The unit cell parameters are a=11.9547(6) Å, b=12.8482(7) Å, c=16.1313(8) Å, α=89.532(1)°, β=72.007(1)° and γ=68.066(1)°. The crystal system of the complex 2 is monoclinic with space group P21lc and four molecules per unit cell. The unit cell parameters are a=14.0273(8) Å, b=11.2184(6) Å, c=12.9441(8) Å and β=102.177(5)°. The complex 1 is a binuclear mixed-ligand system in which both phen and (pydc)2− have contributed to the molecular structure as tri- and bi-dentate ligands, respectively. The complex 2 is a polymeric system in which only one of the fragments of LH2 has acted as a ligand. In both complexes 1 and 2 a large number of hydrogen bonds are observed. These interactions especially in case of complex 2 play an important role in the formation of self associated systems in the crystal lattices. Results of the potentiometric pH titration studies in aqueous solution strongly confirm the formation of InIII and CeIII complexes in solution with stoichiometries very similar to those of the crystalline complexes 1 and 2, respectively.
Keywords: Indium; Cerium; 1; 10-Phenanthroline; Pyridine-2; 6-dicarboxylic acid; X-ray crystal structure; Hydrogen bonds; Solution studies